STUDY OF THE INFLUENCE OF ULTRASONIC TREATMENT ON FLOTATION PROCESSES (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article examines the influence of ultrasonic treatment (UST) on the efficiency of flotation enrichment of gold from refractory ores. Experimental data showed that ultrasound improves gold liberation, destroys gangue minerals, and enhances gold recovery efficiency. Ultrasonic treatment of the pulp (Ultrasound 40 kHz) for 5 minutes after the second stage of grinding, just before the first main flotation, increased gold recovery into the combined concentrate by 4.21% (from 81.08% to 85.29%) and reduced the gold content in tailings from 0.37 g/t to 0.28 g/t. This opens new opportunities for more efficient processing of low-grade ores and tailings.